Dilemma in distance learning during the covid-19 pandemic: The EFL teachers’ perspective - Habib, Arvan Permana; Alek, Alek (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2023)
The dilemma in teaching has been long discussed in the discourse of education, yet the topic has received little attention concerning online teaching, especially during the latest The Covid-19 pandemic. Addressing the gap, the study utilized interview and document analysis that organized following Schwab’s curriculum commonplaces to discover the dilemma encountered according to the perspective of English teachers of SMPN 6 Tangerang Selatan in distance learning during the Covid-19 pandemic situation. The result of interview of four on-duty EFL teachers of SMPN 6 Tangerang Selatan and the analysis of the teachers’ lesson plans and the Circular Letter of Ministry of Education and Culture No. 4 Year 2020 showed the dilemma comprised issues of optimizing teachers’ efforts and authority, maximizing learning comprehension, developing favorable attitudes, maximizing learning time usage, maintaining the children’s academic availability, maintaining a motivating environment for students, and offering academic opportunity for students. The findings inferred a central conflict between teachers’ interests and expectations of the curriculum. From the account of the teachers, they tackled the conflict by improving their IT skills and modifying the learning schedules. However, since the conflict was dilemmatic, the two solutions of teachers still left residual problems both for the teacher and the students.